Controle automático e monitoramento de temperatura em lançamento de efluentes utilizando a plataforma arduino - Martins, Clever Hipolito (2021)
The main form of disposal of industrial effluents is their direction to water bodies, which cause impacts, such as environmental impacts. To control these impacts there are norms and laws that establish standards for effluent discharge, such as control of O2, COD, BOD, pH, temperature, among others. As mentioned, one of the parameters regulated for effluent discharge is temperature, in which, in general, the control and analysis of this variable is done manually in most industries. The proposal of the present work is to build and evaluate a prototype of temperature control for effluent discharge using the Arduino platform, evaluating its behavior in relation to the boundary conditions required by the environmental legislation. The prototype presented good results, with a good precision of opening and closing of the valve, and the valve closing only happened when the liquid (effluent) exceeded 40 °C, the temperature variation in the receptor body was not significant.